Pengaruh Kualitas Pelayanan dan Fasilitas terhadap Kepuasan Pengguna Mikrotrans Jaklingko 01 Rute Tanjung Priok-Plumpang Jakarta Utara (International Forum of Researchers and Lecturers, 2025)
Mikrotrans Jaklingko is one of the public transportation modes managed by PT Transjakarta and is designed as an alternative solution to meet the daily mobility needs of urban communities. Unlike conventional public minibuses (angkot), the Mikrotrans service operates with stricter regulations, such as fixed routes, designated stops, and more orderly service management. The program aims to encourage people to shift from using private vehicles to public transportation while improving user comfort and satisfaction in the Jakarta metropolitan area. This study specifically analyzes the influence of service quality and facilities on user satisfaction with the Mikrotrans Jaklingko service. The research employed a quantitative approach, with data collected through field observations and questionnaires distributed to 100 active Mikrotrans users. The data were processed and analyzed using SPSS through a series of tests, including validity, reliability, classical assumption testing, coefficient analysis, multiple linear regression, and hypothesis testing using both t-tests and F-tests. The findings reveal that service quality has a significant effect on user satisfaction. Furthermore, the available facilities, such as vehicle comfort, safety, and the adequacy of supporting infrastructure, also have a positive and significant effect on satisfaction levels. Simultaneously, both independent variables contribute significantly to enhancing user satisfaction. These results highlight that improving service quality and facilities should be a strategic priority to ensure greater comfort for the public when using Mikrotrans. Ultimately, these improvements will strengthen government efforts to encourage a transition from private vehicles to public transportation in Jakarta, thereby supporting sustainable urban mobility.